Tissue reaction against implantation of nanocomposite and giomers - Vilvarajah, Anusha S; Djustiana, Nina; Widyaputra, S. Sunardhi (Universitas Padjadjaran, 2011)
Dentistry today has inherited technological advancement from other Dental Material sciences, examples are Nanocomposite and Giomers. Nanocomposites and Giomers are common materials used in Dentistry. But what are the implications when these materials are used in practice? The aim for this the study shows the analysis of tissue reaction due to implantation of Nanocomposite and Giomers. The subcutaneous tissue of a mouse is substituted with the human gum tissues. In the experimental group, Nanocomposite and Giomers were implanted in the subcutaneous tissue abdomen region in mice. The slides were made from the surrounding of implantation for both experimental and control groups. The evaluation of the effects of the implant is done in a time interval. Evaluated time intervals are 24 hours, 7